Benjamin Disraeli Letters : 1838-1841, Volume 3 - Disraeli, Benjamin, 1804-1881 (Book collections on Project MUSE., 1987)
Part of the critically acclaimed Letters of Benjamin Disraeli series. This volume contains or describes letters written by Disraeli between 1838 and 1841.